Gender differences in post-competition honesty—An experimental analysis - Giamattei, Marcus; Werner, Katharina (Frontiers in Behavioral Economics, 2024)
While competition is an inherent element of most market activities and immanent in many organizations, competitive incentives may bring about negative externalities, such as unethical behavior. This study examines whether competition affects subsequent honesty in an unrelated task, focusing on gender differences. Our experiment, which includes a real effort task under piece rate and competitive compensation schemes, reveals no overall treatment effects on honesty. However, competition affects men and women differently: women become more honest, while men become (insignificantly) more dishonest. This results in a gender gap in post-competition honesty and, therefore, in payoffs, highlighting the importance of carefully designing incentive schemes that consider gender-specific responses.